2017
DOI: 10.1590/2179-8087.117614
|View full text |Cite
|
Sign up to set email alerts
|

Carbono, Nitrogênio, Abundância Natural de Δ13C e Δ15N do Solo sob Sistemas Agroflorestais

Abstract: RESUMOO objetivo deste trabalho foi avaliar alterações nos teores de C e N e abundância natural de δ 13 C e δ 15 N de um Cambissolo Háplico Tb distrófico em uma área com sistema agroflorestal (SAF). Em cada área de estudo foram coletadas amostras de solo, em 8 profundidades de 0,0-1,0 m. O delineamento experimental utilizado foi o inteiramente casualizado, em esquema de parcelas subdivididas 2 × 8 (2 áreas florestais e 8 profundidades), com três repetições. Com exceção da camada superficial do solo (0,0-0,10),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…Guo et al ( 2020) also found higher carbon contents in subsurface layers when evaluating the carbon vertical distribution in an agroforestry. Couto et al (2017) attributed the higher carbon stocks in deeper layers to a higher degree of maturity and processing of this carbon by microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Guo et al ( 2020) also found higher carbon contents in subsurface layers when evaluating the carbon vertical distribution in an agroforestry. Couto et al (2017) attributed the higher carbon stocks in deeper layers to a higher degree of maturity and processing of this carbon by microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…The higher levels of CMIC, NMIC, MICq and fungal spores found in the soil under native forest are justified by the higher OCC content and quality, MICq which indicates the quality of soil organic matter [4]. In native forest areas there is a higher volume of litter and roots, which promote increased species diversity [29], organic matter content and nutrient availability [7].…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment of δ 15 N values in subsurface can also be attributed to transformations from organic N to mineral N. Thus, as the reactions of mineralization, nitrification, denitrification and volatilization occur associated with N assimilations by plants, there is greater decomposition of the isotope 14 N, leaving the remaining organic matter enriched in 15 N atoms (Couto et al, 2017). Therefore, isotropic values of δ 15 N serve as an indication of the decomposition of organic matter, as the highest values of δ 15 N are found in areas with low contents of organic carbon.…”
Section: Table 1 -Pearson's Correlation Between the Variables Bulk Density (Bdmentioning
confidence: 99%